Penerapan Pembelajaran Musikalisasi Puisi Berbasis Calempong terhadap Kemampuan Membaca Puisi - Hasminur Hasminur; Hasnah Faizah; Elmustian Elmustian; Syafrial Syafrial (Departement of Mathematics Education, 2023)
The discussion of this study explains the results of the research that has been carried out. In this first cycle, the indicators for interpreting ability, articulation, intonation, diction, expression, and totality were inadequate or still in the moderate category. Even so, learning in the first cycle of action has not been achieved but has experienced an increase. The reflection results from the first cycle can be used as a reference for implementing the second cycle class treatment. The implementation of the second cycle of class treatment has been fully achieved and has increased as expected in all indicators. Based on the results of the first and second cycle d, it can be concluded that the application of calempong-based poetry musicalization learning can improve the poetry reading ability of class XI students of SMKN I Bangkinang. This can be seen from the increase in indicators of the ability to read poetry in learning Indonesian.